1949
DOI: 10.1139/cjr49d-013
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Waterfowl in British Columbia Green-Winged Teal

Abstract: The migrations of the Pacific Coast population of Anas carolinensis parallel in time and space those of Anas acuta. Both use the same migration routes along the coast and along the main north and south river systems of the interior. So also both nest more commonly in Alaska than elsewhere. The peak of the spring migration usually is reached in late March or early April; the peak of the autumn migration usually is in late October and early November. A relatively large number normally winter on the Coastal Plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This later migration of juveniles has been noted in redwings (Agelaius phoeniceus) (Allen, 1914), buffle-head (Munro, 1942) and other species, and very likely contributed to the apparent sex-ratio variation in the common golden-eye, buffle-head and common merganser in our study. Although juvenile males of these species were separated whenever possible, some were probably confused with females.…”
Section: Observationsmentioning
confidence: 67%
“…This later migration of juveniles has been noted in redwings (Agelaius phoeniceus) (Allen, 1914), buffle-head (Munro, 1942) and other species, and very likely contributed to the apparent sex-ratio variation in the common golden-eye, buffle-head and common merganser in our study. Although juvenile males of these species were separated whenever possible, some were probably confused with females.…”
Section: Observationsmentioning
confidence: 67%
“…Gadwalls exhibited a similar pattern of habitat use by pairs and broods. Munro (1949) noted that wigeon prefer to nest around certain lakes or marshy sloughs that are surrounded by dry Carex meadows, in which the nests are placed. Unlike most dabbling ducks, females and young frequent the open water of marshy ponds, lake bays, or marsh-edged rivers, with this preference for open water perhaps related to the commensal foraging relationship between wigeons and diving waterfowl.…”
Section: Distribution and Habitatmentioning
confidence: 99%
“…He found that 81 percent of 21 nests were in Juncus cover, while the rest were in mixed prairie or weeds. Munro (1949) also stated that nests are frequently placed in sedge meadows, and Phillips (1924) mentioned that the nest is often located at the base of a tree. Wishart (1983a) noted that 80 percent of the 30 nests he studied in Saskatchewan were under dense stands of shrubs.…”
Section: General Biologymentioning
confidence: 99%
See 2 more Smart Citations